The same as it ever was ? A chance for creating new qualities in our exchanges - Lang, Holger (2022)
(...) Since then, the academic world has undergone some radical changes, and the process is not near its conclusion. Academia is a very close-knit environment, proud of its conditions and requirements, methods, and procedures. Still, the impact of the Covid-19 pandemic is providing unexpected possibilities to develop, question and reform central elements of it.